2022
DOI: 10.3390/cancers15010027
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin-6, a Reliable Biomarker for Predicting the Prognosis of Patients with Cancer and the Effectiveness of Immunotherapy

Abstract: Syntaxin-6 (STX6), a vesicular transport protein, is a direct target of the tumor suppressor gene P53, supporting cancer growth dependent on P53. However, STX6′s function in the tumor microenvironment has yet to be reported. In this research, we comprehensively explored the role of the oncogene STX6 in pan-cancer by combining data from several databases, including the Cancer Genome Atlas, CPTAC, cBioPortal, and TIMER. Then, we verified the carcinogenic effect of STX6 in hepatocellular carcinoma (HCC) and color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Previously, STX6 has been shown to be upregulated in several types of tumors, including HCC, colorectal cancer, pancreatic ductal adenocarcinoma, and esophageal cancer [14,[16][17][18][19]. Consistent with these studies, we found that STX6 was highly expressed in HCC tissues compared with paracancerous tissues and the protein level of STX6 was also increased in cancerous tissues.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Previously, STX6 has been shown to be upregulated in several types of tumors, including HCC, colorectal cancer, pancreatic ductal adenocarcinoma, and esophageal cancer [14,[16][17][18][19]. Consistent with these studies, we found that STX6 was highly expressed in HCC tissues compared with paracancerous tissues and the protein level of STX6 was also increased in cancerous tissues.…”
Section: Discussionsupporting
confidence: 90%
“…In papillary renal cell carcinoma, STX6 promotes tumor tissue angiogenesis, cell proliferation, and migration [15,26], possibly by regulating VEGFR2. STX6 is upregulated in HCC and colorectal cancer, and knockdown of STX6 suppresses cell proliferation, migration, invasion, and cell cycle progression of BEL-7404 HCC cells and HCT116 colorectal cancer cells [16]. In HCC, STX6 expression was significantly correlated with tumor size, Edmondson grade, alpha-fetoprotein level and poor prognosis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation